ANALISIS PEMAHAMAN KONSEP SISWA PADA MATERI HUKUM NEWTON DI SMA NEGERI 3 BENGKAYANG - Sandra, Ella; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine students 'understanding of aspects of understanding in understanding Newton's legal concepts and knowing the factors that cause students' lack of understanding in SMA Negeri 3 Bengkayang class X MIPA totaling 30 students. This type of research is simple descriptive research. Found the percentage of score overall answers students do not understand Newton's legal concept of 67.8%. Judging from every aspect of understanding, the extrapolation aspect has a higher level of difficulty compared to the translation and interpretation aspects. The cause of students not understanding in understanding the concept include students not understanding the concept, not understanding the relationship between concepts, not understanding and interpreting formulas, and lack of teachers in giving questions in the form of understanding concepts.Keywords: Analysis, Understanding, Translation, Interpretation, Extrapolation.